2001
DOI: 10.1111/0002-9092.00228
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Housing Prices, Wages, and Commuting Time on Joint Residential and Job Location Choices

Abstract: An empirical model of joint decisions of where to live and where to work demonstrates that individuals make residential and job location choices by trading off wages, housing prices, and commuting costs. Wages are higher in metropolitan markets, but housing prices are also higher in urban areas. Consumers can live in lower priced nonmetropolitan houses and still earn urban wages, but they incur commuting costs that increase with distance from the city. Improvements in transportation that lower commuting time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 21 publications
(2 reference statements)
4
71
0
2
Order By: Relevance
“…However, it is reasonable to treat households as price-takers in labor and housing markets and, thus, the effects of wages and housing prices on migration decisions can be measured in studies using household data. In such studies, higher relative wages or income are consistently found to increase the probability that a household will select a given location, all else equal (Berger and Blomquist 1992, Davies et al 2001, So et al 2001, Hunt and Mueller 2004, Bayer et al 2008, Bishop 2008, Kennan and Walker 2009, Dahl and Sorenson 2010. In contrast, the results for housing prices are much less clear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it is reasonable to treat households as price-takers in labor and housing markets and, thus, the effects of wages and housing prices on migration decisions can be measured in studies using household data. In such studies, higher relative wages or income are consistently found to increase the probability that a household will select a given location, all else equal (Berger and Blomquist 1992, Davies et al 2001, So et al 2001, Hunt and Mueller 2004, Bayer et al 2008, Bishop 2008, Kennan and Walker 2009, Dahl and Sorenson 2010. In contrast, the results for housing prices are much less clear.…”
Section: Introductionmentioning
confidence: 98%
“…While housing prices clearly matter for moves in both cases, we are primarily interested in their effect on migration at the scale of metropolitan areas, counties, and states. Intra-area studies that examine effects of housing prices on household location decisions include Chan (2001), So et al (2001), Engelhardt (2003), Seig et al (2004), andFerreira et al (2010). 2 Chen and Rosenthal (2008) construct area-level quality of life indices that reflect wages and housing prices.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the commuting distances of older individuals are generally shorter than those of younger persons (Manaugh et al, 2010;Plaut, 2006;Susilo and Maat, 2007), supposedly since younger workers are more likely to have the energy required to realize lengthy, time-consuming commutes (So et al, 2001). …”
Section: Location Of Residence D Sw D Sr D Wr the Determinants Of Thementioning
confidence: 99%
“…Correspondingly, Venhorst et al (2011) established that female college graduates are more likely than their male equivalents to cover large college-to-work distances when starting their first job after graduation. At the same time, females generally have shorter commutes than males (Crane, 2007;Manaugh et al, 2010;Plaut, 2006;Sang et al, 2011;Shuttleworth and Gould, 2010;Susilo and Maat, 2007), possibly due to the gender-specific allocation of domestic responsibilities (Rouwendal and Nijkamp, 2004;Schwanen et al, 2002;, or because women tend to attach a larger value on the disutility of commuting than men (So et al, 2001). We thus hypothesize that the distance between a graduate's place of study and workplace will be larger for female graduates and, since we expect women to have shorter commutes, we assume their college-to-residence distances to be longer than those of men.…”
Section: Location Of Residence D Sw D Sr D Wr the Determinants Of Thementioning
confidence: 99%
See 1 more Smart Citation